Assessment of Healthcare Providers on the Extent of Essential Intrapartum and Newborn Care (EINC) Implementation among Postpartum Mothers in Cavite, Philippines: An Evaluation - Prowel, Mary Grace (JPAIR Multidisciplinary Research, 2017)
Improved medical care and services are some of the strategies that provide quality healthcare to women provided by the government. Such approach in the form of Essential Intrapartum and Neonatal Care (EINC) had reduced infant mortality from 57 every 1,000 live births in 1990 to 14 in 2011. However, maternal deaths have been unacceptably high as it has increased from 162 in 2006 to 211 in 2011 (NCSB, 2011). The study investigated, through a survey, the extent of the implementation of EINC as perceived by the healthcare providers and as assessed by post-partum mothers in Cavite. It also wanted to know if health vectors such as mother’s education, the number of pregnancies, improved medical care and services are some of the strategies that provide quality healthcare to women provided by the government. Such approach in the form of Essential Intrapartum and Neonatal Care (EINC) had reduced infant mortality from 57 every 1,000 live births in 1990 to 14 in 2011. However, maternal deaths have been unacceptably high as it has increased from 162 in 2006 to 211 in 2011 (NCSB, 2011). The study investigated, through a survey, the extent of the implementation of EINC as perceived by the healthcare providers and as assessed by post-partum mothers in Cavite. It also wanted to know if health vectors such as mother’s education, the number of pregnancies, age, sex, and income influence their assessment of the implementation of EINC. Sixty-five (65) healthcare providers and 72 post-partum mothers participated in the study.